If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (6f + -1k) = 0 Remove parenthesis around (6f + -1k) 6f + -1k = 0 Solving 6f + -1k = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add 'k' to each side of the equation. 6f + -1k + k = 0 + k Combine like terms: -1k + k = 0 6f + 0 = 0 + k 6f = 0 + k Remove the zero: 6f = k Divide each side by '6'. f = 0.1666666667k Simplifying f = 0.1666666667k
| 36m^6+12m^4=m^2+0 | | 8r^2+10r-12=0 | | 10x+3=100 | | 5[3(x+4)-2(1-x)]-x-35=14x+65 | | 1.3-5r=7.8 | | 250x^3+128= | | 5y+6y-81=7y+102+66y | | 4a=3a+20 | | fx=(400+20x)(90-1x) | | (3q-8)(-9q+2)(q-2)=0 | | -2x^2=12x-14 | | 5+3*4-8+2*7= | | 2[9(6-5)]= | | (14x+5)(14x+5)=20 | | 2(x+4)+star=16 | | 5f=f+36 | | 5x+5(2x+10)=10x+12 | | 2(x+4)-5x=23 | | 3x+2star+x=x+6 | | 5x-2=-x+7+6 | | 5(y+5)-5y=31 | | -3+sy=17 | | 8x-1x=7x | | 32-(2c+4)=2(c+7)+c | | ax+by+c+2ax-3by+c+by-c= | | 5=(7-2)/3-x | | 2x^2-13=7x | | 5=7-2/3-x | | 3(2star)-3star+4=2star+5 | | 4a+2b+c=8 | | 12-4(6x-2)=8-(2x+5) | | 35=5u |